Effect of Tactile Imitation Guidance on Imitation and Emotional Availability. A Case Report of a Mother and Her Child With Congenital Deafblindness - Peltokorpi, Sini; Daelman, Marlene; Salo, Saara; Laakso, Minna (Frontiers in Psychology, 2020)
Interaction between parents and children with congenital deafblindness (CBD) is easily hampered due to dual sensory loss. This case report examines imitation and emotional availability in interaction between a mother and her three-year-old child with CBD first in unguided play and then in three play sessions with tactile imitation guidance. The video recorded play sessions were analysed for frequency, length and modality of imitation. Emotional Availability Scales were used to code the emotional quality of interaction. The results showed that before the guidance the mother imitated the child mainly vocally. After the guidance, the use of tactility in imitations increased. Imitation exchanges lasted longest in the last session. The emotional availability between the mother and the child was higher after the guidance. Further research is needed to confirm the positive outcomes of this case study.